REDUPLICATION PATTERNS IN THE UTTERANCE OF MANDURO SOCIETY - Ika Lusi Kristanti; Diana Mayasari (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2018)
Reduplication is usually used by society in daily communication. Principally, reduplication relates with word formation. In reduplication, we need to consider the base of the word, the change of phoneme, and the use of affixation. For example: the base word of “rumah” becomes “rumah-rumah”. “Rumah-rumah” means many houses. It can called reduplication, but it does not change the phoneme and does not use affix. This phenomenon occurs in the utterance of Manduro society. Thus, researchers conduct the research in reduplication pattern in the utterance of Manduro society. Descriptive qualitative research is a research type choosen by the researchers. In this case, the researchers use purposive sampling technique in determining the sample of the research. In collecting the data, the researchers use interview, recording, observation, and Swadesh Morris questionnaire to obtain the vocabulary. Meanwhile, data analysis technique used by researchers is inductive analysis with data classification: the use of padan and agih methods, reduction, the scope of theory, and conclusion. Based on the result of the research, there are some reduplication patterns in the utterance of manduro society, such as: full reduplication and partial reduplication